Word Biblical Themes Collection : 15-Volume Set /: 15-Volume Set. (2020) - Allen, Leslie C; Dr, Bauckham, Dr. Richard; Beasley-Murray, George R; Dr, Braun, Dr. Roddy; Butler, Trent C; Dr, Durham, Dr. John I; Dr, Goldingay, Dr. John; Hawthorne, Gerald F; Dr, Hobbs, Dr, T. R; Michaels, J. Ramsey; Morris, Leon, 1914-2006; Smith, Ralph; et al.
No abstract available